The thanks of the fatherland : German veterans after the Second World War - Diehl, James M. (University of North Carolina Press, 1993)
German veterans never embraced the Weimar Republic, created out of the ruins of World War I. Former soldiers demanded a state that was militant, nationalist, and authoritarian, and their rejection of the new democratic Republic played a major role in its collapse and the Nazi rise to power. After Hitler's defeat, German veterans again represented a source of social instability and a potential threat to democracy.